2021
DOI: 10.3390/v13112219
|View full text |Cite
|
Sign up to set email alerts
|

G-Quadruplexes Formation at the Upstream Region of Replication Origin (OriL) of the Pseudorabies Virus: Implications for Antiviral Targets

Abstract: Pseudorabies virus (PRV) is the causative agent of Aujeszky’s disease, which still causes large economic losses for the swine industry. Therefore, it is urgent to find a new strategy to prevent and control PRV infection. Previous studies have proven that guanine (G)-rich DNA or RNA sequences in some other viruses’ genomes have the potential to form G-quadruplex (G4), which serve as promising antivirus targets. In this study, we identified two novel G4-forming sequences, OriL-A and OriL-S, which are located at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…We used TMPyP4 as well as PhenDC-3, another G4 stabilizing agent, to confirm the impact of G4 stabilization on lytic replication. PhenDC3 has also been extensively studied as a G-quadruplex stabilizing agent in altering cellular and viral genome processes ( 71 73 ). We analyzed the effect of G-quadruplex stabilization through the detection of lytic genes as a reduction of lytic DNA replication impacts the transcription of lytic genes.…”
Section: Resultsmentioning
confidence: 99%
“…We used TMPyP4 as well as PhenDC-3, another G4 stabilizing agent, to confirm the impact of G4 stabilization on lytic replication. PhenDC3 has also been extensively studied as a G-quadruplex stabilizing agent in altering cellular and viral genome processes ( 71 73 ). We analyzed the effect of G-quadruplex stabilization through the detection of lytic genes as a reduction of lytic DNA replication impacts the transcription of lytic genes.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have reported G4 formation in DNA viruses such as HSV, an alphaherpesvirus with a double-stranded DNA genome, which exhibits peak G4 formation during the virus replication stage ( 61 ). Previously, we reported G4 formation in pseudorabies virus, an HSV homolog, where G-rich sequences fold into G4s during replication ( 20 , 21 ). In addition to DNA G4s, it has been shown that G-rich RNA sequences are prone to forming RNA G4s as there is no complementary strand to complete base pairing.…”
Section: Discussionmentioning
confidence: 99%
“…The G4 structure consists of stacking tetrads composed of four guanine bases connected by Hoogsteen hydrogen bonds ( 18 , 19 ). Growing evidence indicates the presence of G4s in viral genomes, including pseudorabies virus ( 20 , 21 , 22 , 23 ), HIV ( 24 ), Epstein-Barr virus ( 25 ), human papillomavirus ( 26 ), hepatitis B virus ( 27 ), HSV ( 28 ), Nipah virus ( 29 ), hepatitis C virus (HCV) ( 30 ), Zika virus ( 31 , 32 ), Ebola virus ( 33 ), chikungunya virus ( 34 ), enterovirus A71 ( 35 ), Kaposi’s sarcoma-associated herpes virus ( 36 ), varicella-Zoster virus ( 37 ), severe acute respiratory syndrome (SARS)-CoV ( 38 ), and SARS-CoV-2 ( 39 , 40 ). These G4 structures play vital roles in regulating virus replication, transcription, and translation.…”
mentioning
confidence: 99%